Pengembangan Executive Function Anak Melalui Pekerjaan Rumah Tangga - Hayati, Miratul (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2025)
This study aims to explore children's involvement in household chores and their impact on executive functions. The research method used is a phenomenological approach with in-depth interviews as the data collection technique. The research subjects comprise 8 parents with children aged 6-8 years, residing in both urban and rural areas. Data analysis was conducted using thematic analysis to identify the main themes emerging from the subjects' experiences. The results of the study show that children's involvement in household chores provides experiences that enrich the development of their executive functions. Children who regularly engage in household tasks show improvements in independence, responsibility, problem-solving skills, and self-confidence. Parents reported that setting an example, adjusting responsibilities according to the child's development, and providing clear instructions are effective strategies for involving children in household chores. The study concludes that household chores can be an effective tool for training children's executive functions. The implications of this study are the need for parental education on the importance of children's involvement in household chores and effective strategies to support it. Further research is needed to explore the long-term impact of children's involvement in household chores on the development of their executive functions.